2011
DOI: 10.1111/j.1600-6143.2011.03683.x
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell-Dependent Memory T Cells Impede Nonmyeloablative Mixed Chimerism Induction in Presensitized Mice

Abstract: Presensitization to HLA antigens limits the success of organ transplantation. The achievement of donor-specific tolerance via mixed chimerism could improve outcomes of transplantation in presensitized patients. In presensitized B-cell-deficient μMT B6 mice, we developed nonmyeloablative bone marrow transplantation (BMT) regimens that successfully tolerized presensitized T cells, achieving long-term (LT) multilineage chimerism and tolerance to donor-type skin. To apply these regimens in wild-type (WT) animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…This aspect does not seem to play a critical role in skin graft rejection, but it is generally considered a major problem for bone marrow transplantation in mice (34). For this reason we were not able to induce mixed chimerim in sensitized recipients with circulating donor-specific antibodies (not shown).…”
Section: Discussionmentioning
confidence: 78%
“…This aspect does not seem to play a critical role in skin graft rejection, but it is generally considered a major problem for bone marrow transplantation in mice (34). For this reason we were not able to induce mixed chimerim in sensitized recipients with circulating donor-specific antibodies (not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Evidence of the role of T-cell memory in rejection of bone marrow grafts was shown by Levesque et al . 169 in a murine model. Rejection of bone marrow grafts in allo-presensitized mice was reduced among B-cell-deficient mice, while no reduction in rejection was observed among wildtype mice whose alloantibody had cleared or decreased to minimal levels.…”
Section: The Need For Desensitization In Hsctmentioning
confidence: 99%
“…However, subsequent studies from our and other groups have shown that alloreactive T cell memory is impaired in B cell-deficient mice, suggesting a role for B cells beyond antibody production [35,53,54]. Alloreactive effector T cells developing in the absence of B cells contained fewer IL7Rα − expressing memory precursors, resulting in decreased memory T cell numbers and impaired memory recall [54].…”
Section: Antigen Presentation By B Cells In Transplant Rejectionmentioning
confidence: 94%